Effects of polyphenols and lipids from Pennisetum glaucum grains on T-cell activation: modulation of Ca(2+) and ERK1/ERK2 signaling - Nani, Abdelhafid (BMC Complement Altern Med, 2015)
BACKGROUND: Pearl millet (PM), i.e., Pennisetum glaucum, is widely grown in Africa and known for its anti-oxidant and anti-hyperlipidemic properties. METHODS: The P. glaucum grains were obtained from the region of Ouled Aïssa (South of Algeria).  We assessed the effects of phenolic compounds and lipids, extracted from seeds of P. glaucum, on rat lymphocyte proliferation, activated by phorbol 12-myristate 13-acetate and ionomycin. In order to explore signaling pathway, triggered by these compounds, we assessed interleukin-2 (IL-2) mRNA expression and extracellular signal-regulated kinase-1/2 (ERK1/ERK2) phosphorylation. Finally, we determined increases in free intracellular Ca(2+) concentrations, [Ca(2+)]i, by employing Fura-2/AM in rat lymphocytes. RESULTS: The composition of P. glaucum grains in polyphenols was estimated to be 1660 µg gallic acid equivalents (GAE)/g. Lipids represented 4.5 %, and more than 72% of the fatty acids belonged to unsaturated family. Our investigation showed that both lipid and phenolic compounds inhibited mitogen-induced T-cell proliferation. Compared with phenolic compounds, lipids exerted weaker effects on ERK-1/ERK2 phosphorylation and Ca(2+) signaling in mitogen-activated T-cells. CONCLUSION: We conclude that the immunomodulatory effects of P. glaucum could be contributed by its phenolic and lipid contents.